2017
DOI: 10.1038/bjc.2017.125
|View full text |Cite
|
Sign up to set email alerts
|

Mutation status among patients with sinonasal mucosal melanoma and its impact on survival

Abstract: Background:Sinonasal mucosal melanoma (SNMM) comprises <1% of all melanomas and lacks well-characterised molecular markers. Our aim was to determine the frequencies of common mutations and examine their utility as molecular markers in a large series of primary SNMMs.Methods:SNMM patients seen at our institution from August 1991 through July 2016 were identified. Genomic DNA was extracted from 66 formalin-fixed paraffin-embedded tumours and screened for mutations by direct sequencing. We investigated the associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
49
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 33 publications
10
49
1
Order By: Relevance
“…Likewise, the low prevalence of BRAF mutations in these samples (6.6%) is similar to the 7% and 8% reported by Buery et al and Amit et al in a series from oral and sinonasal melanomas, respectively. Other studies from Italy and Brazil have reported slightly higher frequencies of BRAF mutation in sinonasal (36%) and oral samples (21%) .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Likewise, the low prevalence of BRAF mutations in these samples (6.6%) is similar to the 7% and 8% reported by Buery et al and Amit et al in a series from oral and sinonasal melanomas, respectively. Other studies from Italy and Brazil have reported slightly higher frequencies of BRAF mutation in sinonasal (36%) and oral samples (21%) .…”
Section: Discussionsupporting
confidence: 89%
“…The 4.2% prevalence of KIT mutations in our samples agrees with the minimum value of the range of frequencies previously reported in SNM (4% to 12.5%) but is inferior to the 15% and 27% reported in OM and the 25.9% of other POSNM series . An intriguing finding of this series is the low frequency of KIT mutations (4.2%), despite simultaneously high C‐KIT protein expression.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…To date, only a few studies have evaluated the effect of mutations on mucosal melanoma survival, and the results have been inconsistent. 17,29,30 In our cohort, no statistically significant difference in OS time was detected between the patients with mutations and without mutations.…”
Section: Discussioncontrasting
confidence: 57%